2017
DOI: 10.18671/scifor.v45n114.03
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da poda sobre a qualidade da madeira de Eucalyptus dunnii, Eucalyptus grandis e Eucalyptus saligna

Abstract: ResumoO presente estudo tem como objetivo verificar quantitativamente a qualidade do regime de poda por meio das análises de cicatrização dos ferimentos internos dos nós em razão dos galhos podados. As espécies podadas foram o E. dunnii, E. grandis e E. saligna nas idades de 65, 65 e 52 meses, respectivamente, provenientes de um plantio comercial na região de Rosário do Sul -RS. Foram mensurados e avaliados no corte no plano radial das toras das árvores podadas quanto a extensão da oclusão do nó, a extensão da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In a plantation of Eucalyptus grandis  Eucalyptus urophylla clones in Brazil, tree growth was also reduced with 40 and 60% pruning intensities (Ferraz et al, 2016). Yet, in this same plantation, a 20% pruning intensity improved growth, so that it is deduced that each species has a level at which pruning has favorable and not detrimental effects if properly implemented (Braz et al, 2017). So, the analyzed pruning intensities in P. greggii were probably not the most convenient.…”
Section: La Soledad Canatlán Durango Statementioning
confidence: 93%
See 1 more Smart Citation
“…In a plantation of Eucalyptus grandis  Eucalyptus urophylla clones in Brazil, tree growth was also reduced with 40 and 60% pruning intensities (Ferraz et al, 2016). Yet, in this same plantation, a 20% pruning intensity improved growth, so that it is deduced that each species has a level at which pruning has favorable and not detrimental effects if properly implemented (Braz et al, 2017). So, the analyzed pruning intensities in P. greggii were probably not the most convenient.…”
Section: La Soledad Canatlán Durango Statementioning
confidence: 93%
“…Pruning is a silvicultural practice used in forest plantations to stimulate and regulate the growth of trees, as well as to maintain the shape and density of their crown, ensuring a greater stem height, clean and free of knots (Braz et al, 2017;Ferrere et al, 2015;Ferraz et al, 2016). However, one of the main factors on which its effectiveness depends is the intensity with which it is carried out (Davel, 2013;Erkan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The results for the difference between the indices are greater than those obtained by Stangerlin (2009) and Susin (2012). On the other hand, Rocha and Tomaselli (2002), Rocha andTrugilho (2006), andSouza et al (2015) found no differences in bowing after drying. Considering that the indices after drying are higher than those before drying, it can be said that the water removal process had a greater influence than the cutting.…”
Section: Drying Defectsmentioning
confidence: 94%